Penerapan Alat Test dan Kalibrasi Flowmeter Solar pada Pabrik Pemanggangan Anoda PT INALUM - Windi Febbiyana; Sigit Kurniawan; Maizal Isnen; Seto Anugrah (Jurnal Elektronika Listrik dan Teknologi Informasi Terapan, 2020)
Measuring instrumentation equipment plays an important role. The results of measurements made by several similar measuring instruments do not necessarily show the same results, even though these tools have the same type. The accuracy of all measuring instruments will decrease over time. However, the decrease in accuracy is also caused by the presence of electricity or a hazardous environment. These changes depend on the type of instrument and the environment in which it is used. In order for the instrument to have accuracy in measuring, it is calibrated. Calibrate the solar flowmeter using a recalibrated standard measuring vessel calibrator. Calibration is done by taking flow rate data on the flowmeter which is compared with the measurement results on the standard calibrator. The results of characterization based on the calibration show that the average error reading is 0.01% so that the tool is ready for use.